Steep keratometry and central pachymetry after corneal collagen cross-linking procedure in patients with keratoconus - Resan, Mirko; Vukosavljević, Miroslav; Stanić, Elisaveta; Kovač, Bojan; Ristić, Dragana; Petrović, Maja; Pajić-Eggspuehler, Brigitte; Pajić, Bojan (Vojnosanitetski pregled, 2021)
Background/Aim. Keratoconus is a disorder of the eyewhich results in progressive thinning of the cornea. Thecross-linking procedure (CXL) is applied in the treatment ofinitial progredient forms of keratoconus. It is aiming at increasingbiomechanical stability of corneal stromal tissue toslow down or stop progressing the ectatic disorder. The aimof the study was to examine the effect of CXL procedureon values of steep keratometry (K2) and central pachymetry(CCT) six months after the intervention in keratoconusaffectedpatients. Methods. Clinical prospective cohortstudy included 30 eyes of 29 patients suffering from keratoconus.All patients were examined on Allegro-Oculyzer inorder to diagnose and follow up keratoconus, thus obtainingcorneal topography parameters and parameters importantfor this study: K2 and CCT, preoperatively and sixmonths postoperatively. The CXL procedure was carriedout by following the modified Dresden Protocol. Results.K2 mean value was 49.01 ± 3.99 diopter (Dpt) preoperativelyand 48.06 ± 4.46 Dpt six months postoperatively. K2decreased six months postoperatively by 0.95 Dpt, proportionallyin all patients. Student's paired sample t test showedthat average decrease of K2 (d̄ = 0.95 Dpt) was highly statisticallysignificant (t = 3.381; p < 0.01). CCT mean valuewas 480.17 ± 36.62 μm preoperatively and 444.37 ± 45.01μm six months postoperatively. CCT decreased six monthspostoperatively by 35.8 μm, proportionally in all patients.Student's paired sample t test showed that average decreaseof CCT (d̄ = 35.8 μm) was highly statistically important (t =6.40; p < 0.001)). Conclusion. Application of CXL procedurein the treatment of keratoconus with confirmed progressionhighly reduces steep keratometry and central pachymetrysix months postoperatively. By steep keratometryreducing effect the CXL procedure is efficient in the treatmentof keratoconus, especially its initial stages.
Keywords: keratoconus; corneal topography; corneal pachymetry; collagen